Vignettes of interdisciplinary technical art history investigation - Joyce Hill Stoner (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The Foundation of the American Institute for Conservation oral history archive, which began in 1975, contains almost 300 interviews with pioneer conservators, conservation scientists, and art historians.  Technical examination and technical art history, as exemplified by Roger H. Marijnissen’s publications, has undergone many changes since the 1950s; this article briefly surveys the field, focusing on the examination of easel paintings, with the aid of voices and personal observations from the interviews available in the international oral history archive of the Foundation of the American Institute for Conservation.